Sex-Specific Associations Between Chemotherapy, Chronic Conditions, and Neurocognitive Impairment in Acute Lymphoblastic Leukemia Survivors: A Report From the Childhood Cancer Survivor Study. (3rd September 2020) - van der Plas, Ellen; Qiu, Weiyu; Nieman, Brian J; Yasui, Yutaka; Liu, Qi; Dixon, Stephanie B; Kadan-Lottick, Nina S; Weldon, Christopher B; Weil, Brent R; Jacola, Lisa M; Gibson, Todd M; Leisenring, Wendy; et al.
Abstract: Background: The purpose was to examine associations between treatment and chronic health conditions with neurocognitive impairment survivors of acute lymphoblastic leukemia (ALL) treated with chemotherapy only. Methods: This cross-sectional study included 1207 ALL survivors (54.0% female; mean age 30.6 years) and 2273 siblings (56.9% female; mean age 47.6 years), who completed the Childhood Cancer Survivor Study Neurocognitive Questionnaire. Multivariable logistic regression compared prevalence of neurocognitive impairment between survivors and siblings by sex. Associations between neurocognitive impairment with treatment exposures and chronic conditions (graded according to Common Terminology Criteria for Adverse Events) were also examined. Statistical tests were 2-sided. Results: Relative to same-sex siblings, male and female ALL survivors reported increased prevalence of impaired task efficiency (males: 11.7% vs 16.9%; adjusted odds ratio [OR] = 1.89, 95% confidence interval [CI] = 1.31 to 2.74; females: 12.5% vs 17.6%; OR = 1.50, 95% CI = 1.07 to 2.14), as well as impaired memory (males: 11.6% vs 19.9%, OR = 1.89, CI = 1.31 to 2.74; females: 14.78% vs 25.4%, OR = 1.96, 95% CI = 1.43 to 2.70, respectively). Among male survivors, impaired task efficiency was associated with 2-4 neurologic conditions (OR = 4.33, 95% CI = 1.76 to 10.68) and with pulmonary conditions (OR = 4.99, 95% CI = 1.51 to 16.50), and impaired memory was associated with increased cumulative dose of intrathecal methotrexate (OR = 1.68, 95% CI = 1.16 to 2.46) and with exposure to dexamethasone (OR = 2.44, 95% CI = 1.19 to 5.01). In female survivors, grade 2-4 endocrine conditions were associated with higher risk of impaired task efficiency (OR = 2.19, 95% CI = 1.20 to 3.97) and memory (OR = 2.26, 95% CI = 1.31 to 3.92). Conclusion: Neurocognitive impairment is associated with methotrexate, dexamethasone, and chronic health conditions in a sex-specific manner, highlighting the need to investigate physiological mechanisms and monitor impact through survivorship.